Building a Comprehensive Cancer Education Program to Increase Clinical Capacity in Mozambique - Melissa Lopez; Ellen Baker; Cesaltina Lorenzoni; Elvira Luís; Flora Mabota; Pedro Rafael Machava; José Humberto Tavares; Donato Callegaro Filho; Thiago Celestino Chulam; Kathleen M. Schmeler (2017)
Abstract 8 Background: Worldwide, 14.1 million new cancer cases and 8.2 million cancer-related deaths occur annually. Of global cancer deaths, 65% occur in low- and middle-income countries, where there are not enough medical specialists to provide prevention, screening, and treatment services. For example, there are 245 physicians per 100,000 people in the United States and four physicians per 100,000 people in Mozambique. We undertook this work to investigate how to increase clinical capacity and improve cancer prevention and treatment services to ultimately reduce cancer mortality in Mozambique. Methods: Our education program has three complementary components: Strong partnerships with four academic institutions in Brazil, the Ministry of Health of Mozambique, Maputo Central Hospital, and Mavalane Hospital (Maputo) to develop educational programs and collaborative research; use of technology to implement resource-specific and culturally appropriate telementoring programs; and in-country, hands-on training. Collaboration with Brazilian institutions facilitates communication and provides clinical expertise and program expansion opportunities. The telementoring component uses the Project ECHO model, a program that was developed at the University of New Mexico to engage providers in a horizontal manner through regular case-based discussions. Hands-on training complements the telementoring program and increases the level of expertise. Results: Since January 2015, 120 training hours have been provided through ECHO videoconferences to an average of 11 participants on breast, cervical, and head and neck cancers. Two in-country workshops have provided an average of 1,200 training hours to approximately 100 providers in diagnosis, secondary prevention, and surgical management of breast, cervical, and head and neck cancers, as well as training for medical oncology, oncology nursing, palliative care, and radiation physics. Conclusion: Collaborations with Pink Ribbon Red Ribbon, US academic institutions, and industry partners are being developed to strengthen these programs. Funding: The Cancer Prevention Research Institute of Texas Grant No. PP150012; The University of Texas MD Anderson Cancer Center R. Lee Clark Fellowship award, generously supported by the Jeanne F. Shelby Scholarship Fund; The University of Texas MD Anderson Sister Institution Network Fund (SINF) award; The University of Texas MD Anderson Cancer Center HPV-related cancers Moon Shot program; and The University of Texas MD Anderson Cancer Center Cancer Prevention and Control Platform. AUTHORS' DISCLOSURES OF POTENTIAL CONFLICTS OF INTEREST Melissa S. Lopez No relationship to disclose Ellen S. Baker Stock or Other Ownership: Merck Cesaltina Lorenzoni No relationship to disclose Elvira Xavier Luis No relationship to disclose Flora Mabota No relationship to disclose Pedro Rafael Machava No relationship to disclose Jose Humberto Tavares No relationship to disclose Donato Callegaro Filho No relationship to disclose Thiago Chulam Travel, Accommodations, Expenses: AC Camargo Cancer Center Kathleen M. Schmeler Research Funding: Becton Dickinson Patents, Royalties, Other Intellectual Property: UpToDate